Remodelagem do sistema computacional para dosimetria em radioterapia por nêutrons e fótons baseado em métodos estocásticos - SISCODES - Bruno Machado Trindade (2011)
This work shows the remodeling of the Computer System for Dosimetry of Neutrons and Photons in Radiotherapy Based on Stochastic Methods . SISCODES. The initial description and status, the alterations and expansions (proposed and concluded), and the latest systemdevelopment status are shown. The SISCODES is a system that allows the execution of a 3D computational planning in radiation therapy, based on MCNP5 nuclear particle transport code. The SISCODES provides tools to build a patient's voxels model, to define a treatment planning, to simulate this planning, and to view the results of the simulation. The SISCODES implements a database of tissues, sources and nuclear data and an interface to access then. The graphical SISCODES modules were rewritten or were implemented using C++ language and GTKmm library. Studies about dose deviations were performed simulating a homogeneous water phantom as analogue of the human body in radiotherapy planning and a heterogeneous voxel phantom, pointing out possible dose miscalculations. The Soft-RT and PROPLAN computer codes that do interface with SISCODES are described. A set of voxels models created on the SISCODES are presented with its respective sizes and resolutions. To demonstrate the use of SISCODES, examples of radiation therapy and dosimetry simulations for prostate and heart are shown. Three protocols were simulated on the heart voxel model: Sm-153 filled balloon and P-32 stent, to prevent angioplasty restenosis; and Tl-201 myocardial perfusion, to imaging. Teletherapy with 6MV and 15MV beams were simulated to the prostate, and brachytherapy with I-125 seeds. The results of these simulations are shown on isodose curves and on dose-volume histograms. The SISCODES shows to be a useful tool for research of new radiation therapy treatments and, in future, can also be useful in medical practice. At the end, future improvements are proposed. I hope this work can contribute to develop more effective radiation therapy treatments.